The Plan-Do-Check-Action Approach Model for Quality Management in Community Learning Activity Centers - Wiharjo, Suyadi Murdi; Wulandari, Dian (Journal of Multi-Disciplines Science, 2023)
Quality management is essential for the Center for Community Learning Activities (PKBM) as an entity that runs out-of-school education programs in packages A, B and C. One approach to quality management is the Plan-Do-Check-Action (PDCA) model. This study aims to describe the PDCA model for PKBM quality management. The method used in this study is qualitative, with a descriptive approach and a literature study. Data were obtained from Google Scholar reference journal articles in the 2011-2022 publication period. Articles were searched using the Publish or Perish application with the "PDCA PKBM" keyword. The study results show that the PDCA approach is related to the quality management of an entity. PKBM has applied the PDCA concept in improving the quality management of its entities. The government must support improving PKBM quality management by implementing the PDCA approach. It is an effort to increase the effectiveness of monitoring and quality control activities and PKBM's contribution to increasing the Human Development Index (IPM)